Studi Literatur: Aktivitas Senyawa [6]?Gingerol dari Rimpang Jahe (Zingiber officinale) sebagai Imunomodulator - Nanda Uswatun Hasanah; Dewi Rahmawati; Yurika Sastyarina (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
Immunomodulator is a substance that can change or affect the body's immune system to normal. One of the plants that has immunomodulatory activity is ginger rhizome. Ginger rhizome (Zingiber officinale) is a tribe of Zingiberaceae which is widespread in Southeast Asia, empirically used as a cooking spice and traditional medicine to treat various medical conditions such as diabetes, arthritis, rheumatism, soreness, sore throat, constipation, indigestion, hypertension, dementia, fever, infectious diseases, and helminthiasis. The purpose of this study is to examine the literature regarding the compound [6] -Gingerol from ginger rhizome which has immunomodulatory activity. This research method is a literature study conducted by an online search process using the Google Chrome application, journals obtained on the ScienceDirect, PubMed, and Google Scholar. The journals are national and international journals without any publication time limit for cited journals. There are 7 pieces of literature showing that the compound [6] -Gingerol from ginger rhizome (Zingiber officinale) has activity as an immunomodulator.